Struktur Komunitas dan Serangan Hama-Hama Penting Tanaman Kubis (Brassica oleracea L.) - KUMARAWATI, NI PUTU NIA; SUPARTHA, I WAYAN; YULIADHI, KETUT AYU (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology); Vol.2, No.4, Oktober 2013, 2013)
ABSTRACT The Community of Structure and Attack of Important Pests on Cabbage ( Brassica oleracea L.) The Research community of structure and attack of important pests on cabbage plants was conducted from July to December 2012. The aim of the research was to determine the species diversity, species abundance and attack of important pests on cabbage plants. The research was carried out in two places, namely in the field and in the laboratory. Plant sampling for population of important pests was conducted diagonal method, while plant damage was conducted by the using U-shape method. The number of plant sample were nine plants everyweeks. The diversity of pests was similar on both treatment consisted of six species especially. The six species were Aphis brassicae L.; Crocidolomia pavonana Fab.; Plutella xylostella L.; Spodoptera litura Fab.; Helicoverpa armigera Hubner,, and Chrysodeixis orichalcea L. There were six species that have greater population abundance compare with the are their meanly A. brassicae , P. xylostella and C. pavonana . Population abundance of A. brassicae and P. xylostella that the peak there population in eight weeks C. pavonana whereas peak occurred in week ten. P. xylostella and C. pavonana inflict heavier damage (60.56%) on plants untreated by insecticide compare with crop treated with inseticide (17.25%). Keywords: The community of structure, Attack , Important pests, and Brassica oleracea .
Keywords: the community of structure, attack, important pests, Brassica oleracea